Happy birthday, Felicity! : a springtime story - Tripp, Valerie, 1951-; Andreasen, Dan (Middleton, Wis : Pleasant Co., 1992)
As her tenth birthday approaches, Felicity is excited by her grandfather's visit, but she is also concerned about the growing tensions between the colonists and the British governor in Williamsburg.
"American Girl."
"1774"--Cover.
"Book 4"--Cover.
"Ages 7 and up"--P. [4] of cover
630
Accelerated Reader AR
Keywords: Family life -- Juvenile fiction; Virginia -- Social life and customs -- ca. 1600-1775 -- Juvenile fiction; Williamsburg (Va.) -- Juvenile fiction; Williamsburg (Va.) -- History -- Revolution, 1775-1783 -- Juvenile fiction